USLUB JADAL DALAM AL-QUR’AN DAN IMPLEMENTASINYA DI ERA DIGITAL - Muhamad Ma'ruf Roqqi Amrullah; Niken Larasingtyas; Hamidatul Layla; Kojin Kojin; Ahmad Saddad (LPPM UMC, 2023)
Jadal or debate in the Qur'an is a complex and structured process of discussion, in which arguments, critical thinking, and logic are used to explore the truth and strengthen beliefs. The Qur’an teaches the principles of healthy and fair debate, such as the use of strong evidence, rejection of inappropriate arguments, and respect for the debater. The contemporary implementation of jadal refers to applying the principles of debate taught by the Qur'an in a contemporary context. This involves the use of fact-based arguments, respect for dissent, and the ability to develop a deep understanding of complex issues. By adopting the Qur’anic values of Jadal, modern society can develop critical thinking skills, enhance intercultural dialogue, and create a more productive and meaningful discussion environment. This article uses a descriptive qualitative approach with a literature study design. Data were collected through literature searches using academic databases, some of books, and sources indexed by Sinta, Semantic Scholar and Google Scholar. The data was analysed descriptively by summarising and organising the findings from the selected literature. It was found that jadal has several definitions, types, methods, and its implementation in today's world, especially in the digital era.